2014
DOI: 10.1186/1471-2482-14-85
|View full text |Cite
|
Sign up to set email alerts
|

Can hyperbaric oxygen be used to prevent deep infections in neuro-muscular scoliosis surgery?

Abstract: BackgroundThe prevalence of postoperative wound infection in patients with neuromuscular scoliosis surgery is significantly higher than that in patients with other spinal surgery. Hyperbaric oxygen has been used as a supplement to treat postsurgical infections. Our aim was to determine beneficiary effects of hyperbaric oxygen treatment in terms of prevention of postoperative deep infection in this specific group of patients in a retrospective study.MethodsForty two neuromuscular scoliosis cases, operated betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…24 , though stated as a RCT, is a cohort study by described methodology and thus assessed as such. Of the cohort studies, 26 (81.2%) were retrospective 9,[13][14][15]17,20,22,23,[25][26][27][29][30][31][33][34][35][36][37][38]40,41,44,46,47,49 , 3 (9.4%) were prospective 16,21,24 , and 3 (9.4%) was ambispective 12,43,48 in study design. The number of patients in included RCTs ranged from 30 to 326 (Median: 155), whilst that in cohort studies ranged from 42 to 10,225 (Median: 265.5).…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…24 , though stated as a RCT, is a cohort study by described methodology and thus assessed as such. Of the cohort studies, 26 (81.2%) were retrospective 9,[13][14][15]17,20,22,23,[25][26][27][29][30][31][33][34][35][36][37][38]40,41,44,46,47,49 , 3 (9.4%) were prospective 16,21,24 , and 3 (9.4%) was ambispective 12,43,48 in study design. The number of patients in included RCTs ranged from 30 to 326 (Median: 155), whilst that in cohort studies ranged from 42 to 10,225 (Median: 265.5).…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…Two studies were identified from the literature. One study investigated hyperbaric oxygen 20 , and one study investigated postoperative administration of prostaglandin E1 (PGE1) 12 . The study by Inanmaz et.…”
Section: Q1c What (Non-amp) Pharmacological Measures Can Be Used To mentioning
confidence: 99%
See 3 more Smart Citations